Willingness to pay for soccer player development in the United States - Morgan, A.; Whitehead, J. C. (Journal of Sports Economics, 2018)
American households` willingness to pay (WTP) for soccer player development is measured using the contingent valuation method. Data are drawn from two national surveys administered before and after the 2014 World Cup event. Individuals are asked whether they perceive that additional funding for player development will improve the chances of the national team`s performance at the 2018 World Cup and whether they are willing to pay an annual household tax to fund the program. A bivariate probit model accounts for correlation between the two decisions. WTP estimates indicate that the intangible benefits of player development are roughly twice the cost.